Computationally Identifying Novel NF-κB-Regulated Immune Genes in the Human Genome - Liu, Rongxiang; McEachin, Richard C.; States, David J. (Genome Research, 2003)
Identifying novel NF-κB-regulated immune genes in the human genome is important to our understanding of immune mechanisms and immune diseases. We fit logistic regression models to the promoters of 62 known NF-κB-regulated immune genes, to find patterns of transcription factor binding in the promoters of genes with known immune function. Using these patterns, we scanned the promoters of additional genes to find matches to the patterns, selected those with NF-κB binding sites conserved in the mouse or fly, and then confirmed them as NF-κB-regulated immune genes based on expression data. Among 6440 previously identified promoters in the human genome, we found 28 predicted immune gene promoters, 19 of which regulate genes with known function, allowing us to calculate specificity of 93%–100% for the method. We calculated sensitivity of 42% when searching the 62 known immune gene promoters. We found nine novel NF-κB-regulated immune genes which are consistent with available SAGE data. Our method of predicting gene function, based on characteristic patterns of transcription factor binding, evolutionary conservation, and expression studies, would be applicable to finding genes with other functions.